2020
DOI: 10.1186/s12917-020-02522-0
|View full text |Cite
|
Sign up to set email alerts
|

Wild-type cutoff for Apramycin against Escherichia coli

Abstract: Background: Apramycin is used exclusively for the treatment of Escherichia coli (E.coli) infections in swine around the world since the early 1980s. Recently, many research papers have demonstrated that apramycin has significant in vitro activity against multidrug-resistant E.coli isolated in hospitals. Therefore, ensuring the proper use of apramycin in veterinary clinics is of great significance of public health. The objectives of this study were to develop a wild-type cutoff for apramycin against E.coli usin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…The use of in-feed medications such as antibiotics and ZnO have supported the control of PWD over the last few decades. Among the potential antibiotics to treat PWD, apramycin is indicated to treat porcine colibacillosis and has been widely used since the 1980s ( 4 , 21 ). It is a bactericidal antibiotic within the group of aminoglycosides that inhibits bacterial protein synthesis by irreversibly binding to the receptor proteins on the 30S subunit of the bacterial ribosome ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…The use of in-feed medications such as antibiotics and ZnO have supported the control of PWD over the last few decades. Among the potential antibiotics to treat PWD, apramycin is indicated to treat porcine colibacillosis and has been widely used since the 1980s ( 4 , 21 ). It is a bactericidal antibiotic within the group of aminoglycosides that inhibits bacterial protein synthesis by irreversibly binding to the receptor proteins on the 30S subunit of the bacterial ribosome ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…We therefore investigated the prevalence of swine pathogenic E. coli resistance to these agents. We defined a breakpoint of apramycin at 64 µg/ml (Figure 4A) in the present study, and this breakpoint is reliable because the same concentration was reported by the National Veterinary Assay Laboratory (National Veterinary Assay Laboratory, 2009), Kirby (2016), andYang et al (2020). The National Veterinary Assay Laboratory also determined the MICs of E. coli strains against bicozamycin to be in the range of 0.125-512 µg/ml and set the breakpoint at 128 µg/ml (National Veterinary Assay Laboratory, 2009).…”
Section: Discussionmentioning
confidence: 60%